RELATIONSHIP OF SELF-EFFICACY WITH LEARNING OUTCOMES IN CLASS XI GEOGRAPHY LEARNING SOCIAL SCIENCES STATE SENIOR HIGH SCHOOL 1 SUNGAI RAYA - Tampubolon, Sartika Evalina; Tampubolon, Budiman; Harjanti, Diah Trismi (GEOREFERENCE, 2024)
Person self-efficacy plays a critical part in the learning process, when understudy self-efficiency is improved, students can attain their potential well in case understudy self-efficacy underpins it. The inquiry aims to clarify the relationship between self-efficacy and understudy learning results at SMAN 1 Sungai Raya Lesson XI IPS Geography. The strategy utilized is the expressive quantitative inquiry about connections and relationship studies. This ponder had a test of 107 understudies based on the Harryking Nomogram calculation. Investigate information collection strategies incorporating circuitous communication and documentation studies. The disobedient utilized in this inquiry were surveys and developmental esteem records for Lesson XI IPS Geography understudies at SMAN 1 Sungai Raya as numerous as as 81.28% are within the "great" category in Chapter 1 and 83% are within the "great" category in Chapter 2. In agreement with the facts of factual calculations based on the item minute relationship equation, the relationship between self-efficacy and understudy learning scores can be calculated. The result is rcount=0.643 compared to r table 0.195 at a critical blunder level of 5% in Chapter 1. Then, in Chapter 2 the comes about was r count 0.526 compared to r table 0.195 at a noteworthy mistake level of 5%. Based on the data, it can be concluded that there's a positive relationship between self-efficacy and understudy learning scores at SMAN 1 SungaiRaya in lesson XI IPS Geography.